Skrining Tentang Kehamilan Resiko Tinggi Di RT 24 Kelurahan Sawah Lebar Kecamatan Ratu Agung Kota Bengkulu - Saputra, Aa Deno; Melani, Rina; Sinaga, Uli Astika; Sari, Melta; Herlina, Herlina; Ayu LN, Nimas (Utami Publisher, 2024)
High-risk pregnancy is a dangerous condition that can potentially cause maternal death, such as from bleeding, eclampsia, and infection. High-risk pregnancy remains a health service issue, particularly in the field of obstetrics (Manuaba, 2007). Many high-risk pregnancy cases are found in the community, but healthcare workers cannot identify them one by one; hence, the role of healthcare workers is crucial in detecting pregnant women. One of the actions includes health promotion and risk prevention, such as providing nutritional supplements, iron, tetanus toxoid immunization, and counseling on pregnancy danger signs and family planning. Several risk factors present in a mother can turn her pregnancy into a high-risk one. These risk factors can be minimized and managed with appropriate prenatal care services (Saifuddin, 2005). Factors that pregnant women need to be aware of that can trigger a high-risk pregnancy include maternal age ≤ 20 years and ≥ 35 years, giving birth to four or more children, child spacing ≤ 2 years, height ≤ 145 cm, poor obstetric history, previous cesarean section, mild pre-eclampsia, multiple pregnancies, hydramnios/polyhydramnios, intrauterine fetal death, post-term pregnancy, abnormal fetal position, antepartum hemorrhage, and severe pre-eclampsia/eclampsia.